Relative age effect in male and female elite international amateur boxing - Kim, V.; Pote, L.; Groom, R.; Thomson, E.; Nicholls, S. B. (Journal of Sports Sciences, 2024)
This study aimed to determine whether the Relative Age Effect (RAE) was present in different sexes and age categories in 12 elite-level international amateur boxing competitions. A total of 4813 athletes competing between 2013 and 2022 were analysed. Athletes were split into four quartiles according to their birth date and compared to the expected (equal) birth date distribution using chi-squared goodness of fit. The results revealed greater RAE prevalence in youth compared to the senior group. RAE was more prominent in males compared to females, with the female group showing an inverse RAE trend. Odds ratio (OR) showed an overrepresentation of male boxers born in Q1 compared to Q4 (OR > 1.19-1.33), while senior female boxers presented an inverse trend (OR < 0.95). Odds Ratios for medallists within the youth group were greater than 1.07 (except Q3 × Q4 = 0.93) highlighting an overrepresentation of boxers born earlier in the year. A shift in strategy to reduce the RAE in young boxers whereby coaches focus less on the short-term pursuit of sporting success is encouraged. Organisations and coaches should increase awareness and provide systematic education around RAE, whilst creating equal competitive opportunities for all young boxers to reduce the extent of RAE in boxing.